(untitled) (Herald of Journalism, 2018)
Islam is one of the three world religions that arose in the Middle East in the 7th century AD. The Muslim law had a profound impact on the history of development of the state and law of a number of countries. The author in the article considers first of all religion as a set of world views, views and notions for uniting people. The relevance of the study is determined by the trends of modern socio-cultural development, which give rise to an increased interest in the person of Islam, the development of modern philosophical anthropology, and the problems of complex human studies. Based on the level structure of human nature, they distinguish man as the bearer of the historical values of culture. The purpose of this study is the problems of the influence of Islam on the international legal regulation of relations between Islamic countries and the possibility of using its positive potential in the formation of the international legal order in the current conditions of world development.